Simplified cascade multiphase DC-DC boost power converters for high voltage-gain and low-ripple applications - Pekik Argo Dahono (Institute of Advanced Engineering and Science, 2021)
This paper proposes two new simplified cascade multiphase DC-DC boost power converters with high voltage-gain and low ripple. All simplifications reduce the number of active switching devices from 2N into N, where N is the phase number. The first simplification reduces the number of inductors from 2N into N+1 and increases the number of diodes from 2N into (2N+1). The second simplification reduces the number of inductors from 2N into N+1 and increases the number of diodes from 2N into (3N+1). The second simplification needs inductors with smaller current rating than the first simplification. The expressions of output voltage as a function of load current are derived by taking into account the voltage drops across the inductors and switching power devices. Simulated and experimental results are included to show the basic performance of the proposed cascade multiphase DC-DC boost power converters.